Management Practices of Technological Innovation: proposal of a model for small and medium Brazilian enterprises (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4917.116-146.The search for competitiveness points out at the importance of companies being alert to the external environment and pursuing sustainable competitive advantages based on innovations that are difficult to be imitated by competitors. However, the generation of innovations depends on how it is conducted; their performance depends on management mechanisms to provide innovations aligned with corporate and competitive strategies they are grounded in the context of change. This paper discusses the innovation management practices in small and medium-sized Brazilian companies. Therefore, we carried out a bibliographic research of national and international literature from the fields of business management, management of technology and innovation and small and medium businesses. The result of this research inspired the construction of a technological innovation management model for small and medium businesses proposed in this paper.